2009
DOI: 10.1016/j.jvs.2009.04.069
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative asymptomatic cardiac damage after endovascular abdominal aneurysm repair is associated with poor long-term outcome

Abstract: Asymptomatic cardiac damage in patients undergoing EVAR is associated with poor long-term outcome. Routine perioperative cardiac screening after EVAR might be warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Specifically, in this study, cTnI of more than 0.6 ng/ml and/or cTnT of more than 0.03 ng/ml independently predicted a 2.15-fold and 1.89-fold increase in mortality. Winkel et al [12] confirmed these results by reporting 9% occurrence of asymptomatic cardiac damage in 220 patients undergoing endovascular aortic repair. These patients had a 2.3-fold increase for all-cause mortality during a medial follow-up of 2.9 years.…”
Section: Discussionmentioning
confidence: 83%
“…Specifically, in this study, cTnI of more than 0.6 ng/ml and/or cTnT of more than 0.03 ng/ml independently predicted a 2.15-fold and 1.89-fold increase in mortality. Winkel et al [12] confirmed these results by reporting 9% occurrence of asymptomatic cardiac damage in 220 patients undergoing endovascular aortic repair. These patients had a 2.3-fold increase for all-cause mortality during a medial follow-up of 2.9 years.…”
Section: Discussionmentioning
confidence: 83%
“…8,9 Other studies examining statins specifically in elective AAA repair are few and retrospective in nature. [10][11][12] Most studies of statins and AAA are observational and investigate AAA surveillance and examine aortic growth rates in patients with and without statin therapy. [13][14][15][16] Furthermore, none examine the financial effect of these lipid-lowering agents, whose continued use in noncardiac surgery is advocated in the American Heart Association guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Although the isolated elevation of troponin also has implications on long-term prognosis, the patient should not receive treatment for AMI, but undergo additional cardiological stratification before hospital discharge 32,36,77 .…”
Section: Clinical Findings and Diagnosismentioning
confidence: 99%